2012
DOI: 10.1088/0953-8984/24/40/405504
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of structural and electronic properties of Pr2NiO4through first-principles calculations

Abstract: The structural and electronic properties of bulk Pr(2)NiO(4+δ) (δ = 0 and 0.031) were analyzed using first-principles calculations based on the density functional theory (DFT) for application to electrode materials in solid-oxide fuel cells (SOFCs). Two structures of Pr(2)NiO(4) were analyzed: one in space group I4/mmm associated with the high temperature tetragonal (HTT) structure, and the other in Bmab with the low temperature orthorhombic (LTO) structure. The main difference between the two structures is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
2
14
0
2
Order By: Relevance
“…2(c)). It is worth noting that tilts around the O eq -Ni-O eq axis are expected due to the high amount of interstitial oxygen: indeed as calculated for iso-structural La 2 NiO 4+δ , 38,39 O int shifts the four neighbouring O ap along the bond of about 0.5 Å (see Fig. 2a, red stick) inducing a substantial tilt of the octahedra.…”
Section: Resultsmentioning
confidence: 76%
“…2(c)). It is worth noting that tilts around the O eq -Ni-O eq axis are expected due to the high amount of interstitial oxygen: indeed as calculated for iso-structural La 2 NiO 4+δ , 38,39 O int shifts the four neighbouring O ap along the bond of about 0.5 Å (see Fig. 2a, red stick) inducing a substantial tilt of the octahedra.…”
Section: Resultsmentioning
confidence: 76%
“…Thus, for example in the Ba 1Àx Sr 220,250 Recent first-principles DFT calculations provide a different perspective on how the oxygen vacancy formation energy, mobility, and surface exchange rate vary with perovskite composition. 215,220,241,[250][251][252][253][254][255] One proposed materials descriptor correlating with the high temperature O-reduction rate is the position of the oxygen O-2p-band center measured relative to the Fermi energy. ‡ As shown in Fig.…”
Section: Fundamental Cathode Materials Propertiesmentioning
confidence: 99%
“…[20] (Fig. 4) with antiferromagnetic binding of the magnetic moments of Ni cations (unlike the work by Aspera et al [34]).…”
Section: Isotope Exchange Datamentioning
confidence: 69%
“…E.g., according to DFT calculations for La 2−x Sr x NiO 4+δ , migration barrier for this mechanism varies in the range of 0.5-3 eV depending on Ni cations charge compared to 0.3-0.7 eV for cooperative mechanism (the values are close and even value for oxide-peroxide mechanism is slightly lower for Ni cations charge of 2.5+) [36]. Moreover, there is a certain anisotropy in the oxygen transport: oxygen anions diffusion in a-b plane is faster than along the c axis, significant difference in calculated values of both diffusion coefficient and its effective activation energy being reported [23,[25][26][27][31][32][33][34][43][44][45][46][47][48][49]. For undoped Ln 2 NiO 4+δ , it was demonstrated that octahedral rotations in the structure affect the interstitial oxygen transport in I4/mmm structure with the force constant of these rotations becoming "softer" with decreasing the Ln cation radius (with a minimum for Ln = Gd) [23].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation